2004
DOI: 10.1189/jlb.0204104
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of PSGL-1 attenuates CD14+ monocytic cell recruitment in intestinal mucosa and ameliorates ileitis in SAMP1/Yit mice

Abstract: The pathogenesis of Crohn's disease (CD) is not known. However, monocytes and macrophages are thought to play important roles in the development of mucosal inflammation. Therefore, in this study, we examined the role of monocyte-endothelial cell interactions in senescence-accelerated mouse P1 (SAMP1)/Yit mice, a murine model of spontaneous ileitis. Fluorescence-labeled CD14+ monocytic cells isolated from the spleen and mesenteric lymph nodes of AKR/J (control) mice were injected into the tail veins of recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 38 publications
4
38
0
Order By: Relevance
“…We consider that our findings will contribute to further understand the physiological role of PSGL-1 in the immune system, and the complexity of the different stimuli for the induction of immune tolerance. In addition, our findings may have practical relevance because it has been proposed that PSGL-1 is a potential target for the therapy of autoimmune and inflammatory diseases (41,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…We consider that our findings will contribute to further understand the physiological role of PSGL-1 in the immune system, and the complexity of the different stimuli for the induction of immune tolerance. In addition, our findings may have practical relevance because it has been proposed that PSGL-1 is a potential target for the therapy of autoimmune and inflammatory diseases (41,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors speculated that other adhesion molecules such as LFA-1 and VCAM-1 (ligand VLA-4) may not be key factors in monocyte homing, as their ligands were expressed at lower levels on Ly6C high cells. Furthermore, other studies detected PSGL-1-dependent monocyte migration in the periphery during Leishmania major infection, tumor metastasis, and thrombus formation (48,81,82). Thus, to our knowledge, we investigated for the first time PSGL-1-dependent monocyte recruitment to the CNS.…”
Section: Ccr2mentioning
confidence: 95%
“…The dependence on PSGL-1 for lymphocyte migration is well established (56,57,(79)(80)(81)(82). However, to date, the function of PSGL-1 in monocyte recruitment has not been sufficiently addressed.…”
Section: Ccr2mentioning
confidence: 99%
“…In the model of cold ischemia/ reperfusion, hepatic endothelial neutrophil infiltration and hepatocyte injury were diminished, and the expression of TNF-␣, IL-6, iNOS, IL-2, and IFN-␥ mRNA was decreased in livers pretreated with recombinant PSGL-Ig (36). Other reports showed that blockade of PSGL-1 attenuated macrophage recruitment in intestinal mucosa and ameliorated ileitis in a mouse model of Crohn's disease (37,38).…”
Section: Discussionmentioning
confidence: 82%